LABOMAR: 60 years of service to society: LABOMAR: 60 anos de serviço à sociedade - Bezerra Menezes, Maria Ozileia; de Souza Pinheiro, Lidriana (Arquivos de Ciências do Mar, 2022)
A group of visionary and enthusiastic people started a great project 60 years ago. Led by the young professor Melquíades Pinto Paiva, alongside the biologist Rui Simões de Menezes and the pioneering team of students formed by Hermínia de Castro Holanda, José Fausto Filho, Maria Ivone Mota and Vicente Araújo Barreto, they created the Marine Biology Station at the Federal University of Ceará (UFC), today called Labomar. This project was supported by Dean Antônio Martins Filho, the first dean of the UFC. Nowadays, we are privileged to participate in the celebration of the first 60 years of Labomar and to have the opportunity to write some reflections in this regard.